STRUKTUR DAN KINERJA BPR SYARIAH DI JAWA TIMUR: PERIODE 1996-2002 - Lyla Rachmaningtyas; Sugeng Hariadi (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2005)
This study examines the soundness of the east Java, shariah and credit rural banking system by describing market structure and competitive condition and analyzing factors affecting industrial banking performance. Competition measured by means of traditional industrial organization method, Structure-Conduct-Performance (SCP) model.In order to clarify the assessment of shariah and credit rural banking system, this study apply OLS estimation while variation of the change dependent variable ROA as a profitability measurement expected can be explained by independent variables ASET (bank asset), CAR (Capital Adequacy Ratio), LDR (Loan toDdeposit Ratio), DANA (concentration ratio).Estimation indicates monopolistic competition or cournot oligopoly structure for all five shariah and credit rural banking system by applying panel analysis in period 19962002. The results show factors affecting banking performance are ASET, CAR and LDR. Banking performance that is yield hardly improves society welfare. It is demonstrate from the increased of intermediation cost, NPL and lack of bank and product socialization. Therefore, there is less capacity trust to shariah banking system in east Java.